2019
DOI: 10.1002/ajcp.12329
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Program Quality in a National Sample of After‐school Settings: The Role of Youth–Staff Interactions and Staff/Organizational Functioning

Abstract: Highlights• Staff relational practices mediate relations of organization functioning and perceived quality.• Staffing and organizational processes underlie a culture of positive adult-youth interaction.• Staff identifying with the experiences of youth contributes to youths' perceptions of club quality.• Results underscore the importance of workforce development in after-school programs.Abstract Using multilevel data from the national evaluation of Boys and Girls Clubs of America (BGCA), this study examined ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…There is a general consensus that afterschool instructors (ASI) are critical to the success of programs through their contributions to the overall afterschool quality and student outcomes (Davidson, Evans, & Sicafuse, 2011;Hirsch, Deutsch, & DuBois, 2011;Vandell, Reisner, & Pierce, 2007); in response, there is a growing body of work capturing these frontline perspectives (e.g., Larson, Walker, Rusk, & Diaz, 2015). Kuperminc et al (2019) examined a national sample of ASIs across 740 program sites and found that positive staff-youth relationships were significantly associated with positive youth-reports on aspects of program quality, such as engagement, belonging, and safety.…”
Section: Describing the Afterschool Workforcementioning
confidence: 99%
See 4 more Smart Citations
“…There is a general consensus that afterschool instructors (ASI) are critical to the success of programs through their contributions to the overall afterschool quality and student outcomes (Davidson, Evans, & Sicafuse, 2011;Hirsch, Deutsch, & DuBois, 2011;Vandell, Reisner, & Pierce, 2007); in response, there is a growing body of work capturing these frontline perspectives (e.g., Larson, Walker, Rusk, & Diaz, 2015). Kuperminc et al (2019) examined a national sample of ASIs across 740 program sites and found that positive staff-youth relationships were significantly associated with positive youth-reports on aspects of program quality, such as engagement, belonging, and safety.…”
Section: Describing the Afterschool Workforcementioning
confidence: 99%
“…There has been a recent movement to examine the experiences of the understudied youth-serving workforce, such as afterschool, by taking a "whole-person approach" (Cappella & Godfrey, 2019). Understanding the various ecological factors that influence the development of ASIs can inform approaches to further strengthen and develop their skills (Kuperminc et al, 2019). To contextualize the experiences of ASIs, researchers are encouraged to examine the staff's individual skills, professional interpersonal connections, organizational characteristics of their workplace culture and climate, and other community and societal macro-level aspects that influence their work (Cappella & Godfrey, 2019).…”
Section: Guiding Perspectives and Frameworkmentioning
confidence: 99%
See 3 more Smart Citations